On the Possibility of Using the Chemometric (Discriminant) Method of Analysis in the Comparative Study of Heroin - L. I. Modinova; N. A. Shcherbakov (Теория и практика судебной экспертизы)
The paper aimed to ascertain the possibility of using the chemometric (discriminant) method when analyzing the results of mid-range IR spectroscopy and gas chromatography-mass spectrometry for a comparative study of heroin to establish a common source of origin. The advantage of this method of comparative research in comparison to the existing ones is the reduction in the time for obtaining the result, the clarity and automation of the comparison process, which is essential for the comparative study of a large number of objects and the keeping of the corresponding type of forensic accounting. The paper shows that the results obtained by chemometric processing of data from two non-correlating analysis methods (IR spectroscopy and gas chromatography-mass spectrometry) coincided.